PERANCANGAN INTERIOR KANTIN MODERN UNIVERSITAS HARAPAN MEDAN FAKULTAS TEKNIK DAN KOMPUTER BERBASIS 3D - Muchzakhir Bustari; Sayuti Rahman; Ari Usman (Universitas Methodist Indonesia, 2021)
The era of globalization always changes in terms of knowledge every year. One of them is the presence of technology as a tool to facilitate human work. The use of existing technology is then developed into information. Without information, maybe humans don't know how to see and even use technology as a place for information. One of the information that can be obtained through technology is video. In this video, it will show the interior design of the modern canteen of the engineering faculty and computer fields of the university. With a canteen design using this modern development concept, it can be used as a new canteen development innovation. The canteen's 3D model design is made using a blender software. From this design, animation will be given and implemented into a video. The design process starts from hardware and software, storyboards and sketches, object modeling, presenting textures, presenting animation, rendering, and editing. The final result of the video can be used as promotion or interactive multimedia to the community or certain parties.